Sustainable Energy and Environmental Engineering III - Choi, Seung-Bok; Kim, Yun-Hae (Advanced materials research, 2015)
Collection of selected, peer reviewed papers from the 2013 3rd International Conference on Sustainable Energy and Environmental Engineering (ICSEEE 2014), December 30-31, 2014, Shenzhen, China